Perlindungan Hukum Situs Cagar Budaya Pariwisata Arca Domas Desa Sukaresmi Kabupaten Bogor - Khunaepi, Rivay; Nurwati; Aminulloh, Muhamad (Universitas Djuanda, 2024)
This study aims to determine the legal protection of the Arca Domas cultural heritage tourism site and to find out the obstacles in the management of Arca Domas tourism in Sukaresmi Village. The type of research that the author uses in this research is normative legal research. Normative legal research is legal research conducted using a statutory approach coupled with books, journals, papers, and opinions of legal experts. In the implementation of legal protection of arca domas tourism cultural heritage sites, protection is needed to obtain legal certainty about the protection itself so that there are no disturbances or dangerous things; and to obtain comfort in the legal protection of arca domas tourism cultural sites. Domas statue is one of the cultural sites that must be protected as stipulated in Law number 09 of 2010 concerning cultural heritage. In Article 58 paragraph 1 of Law No. 11 of 2010 concerning Cultural Heritage it is stated that